Relatório de Estágio Profissional - "O desafio de ser Professora" - Joana Raquel Ferreira Mendes da Silva (2018)
The present document portrays the path I took, as a trainee teacher, in the relentless search for "being a Physical Education Teacher". It seeks to convey to its readers all the feelings and experiences lived from the first day I entered the school until the day I left, always in a constant confrontation between the know-how and its related practices, and the reality of the school context in which I found myself. João Gonçalves Zarco Secondary School, in Matosinhos, was the main stage of action of the Internship Core composed of three Trainee Students, each one in charge of a 10th-year class. Also a target of our intervention was the Elementary School of Matosinhos, where the previous referred Core shared a 5th-year class. In terms of structure, the report is divided into seven major parts: 1) "Introduction" - introduces and contextualises the purpose of the document; 2) "Personal Context" - a presentation of me revealing some aspects that led me to choose this profession as well as my pre-internship perspectives, and post-internship reactions; 3) "Professional Practice Context" - refers to the spaces used, and introduces the participants involved; 4) "Execution of the Professional Practice" - my pedagogical practice, how it was organised and the models of teaching associated with it, some problems that I came across with and found necessary to reflect on them, and a note on the importance of reflection; 5) "Involvement in School and Relationships in the Community" - all the work developed in accordance with the School Activities Plan and in School Sports; 6) "STUDY: Students' Perception of Functional Training in Physical Education Classes" - testimonies of several students about the importance of including the Functional Training to which they were subjected in Physical Education classes; and 7) Final Considerations - the end of a stage, the end of my academic training, and perspectives for the beginning of my professional life.